Household Responses to Shocks in Rural Ethiopia Livestock as a Buffer Stock - Ali, Daniel Ayalew (World Bank E-Library Archive, 2015)
This paper uses a stochastic dynamic programming model to characterize the optimal savings-consumption decisions and the role of livestock inventories as a buffer stock in rural Ethiopia. The results show that relatively land-rich households use accumulation and liquidation of cattle and other animal inventories for partial consumption smoothing, while low-income households appear not to do so. The results highlight the need for improvement in livestock markets, which are often affected by high transaction costs and price risk, and for investigation of other approaches to risk management